Further discoveries in the ever-expanding genus Begonia (Begoniaceae): fifteen new species from Sumatra - Mark Hughes; Deden Girmansyah; Wisnu Handoyo Ardi (European Journal of Taxonomy, 2015)
Fifteen new species of Begonia L. from Sumatra are described and illustrated, in Begonia sect. Bracteibegonia (B. beludruvenea M.Hughes sp. nov. and B. jackiana M.Hughes sp. nov.), B. sect. Petermannia (B. harauensis Girm. sp. nov.), B. sect. Platycentrum (B. leuserensis M.Hughes sp. nov.), B. sect. Reichenheimia (B. fluvialis M.Hughes sp. nov., B. halabanensis M.Hughes sp. nov., B. karangputihensis Girm. sp. nov., B. kemumuensis M.Hughes sp. nov., B. korthalsiana Miq. ex M.Hughes sp. nov., B. kudoensis Girm. sp. nov., B. lilliputana M.Hughes sp. nov., B. olivacea Ardi sp. nov., B. raoensis M.Hughes sp. nov., B. simolapensis Ardi sp. nov.) and B. sect. Sphenanthera (B. pseudoscottii Girm. sp. nov.). Using the International Union for the Conservation of Nature criteria, 6 are considered to be Least Concern, 5 Vulnerable and 4 Data Deficient. A key to 58 of the 63 currently accepted Begonia species in Sumatra is provided.